Gastrodia elata blume (Gastrodiae Rhizoma, Tianma) extract for cognitive enhancement in middle-aged adults with normal or mild impairment: A randomized, double-blind, placebo-controlled clinical trial - Hyungsun Jun; Junghan Lee; Byung Ouk Park; Ryeo Won Kim; Jungtae Leem; Kang-Beom Kwon (Journal of Functional Foods, 2025)
Early attention to cognitive impairment is vital. This 12-week, randomized, double-blind, placebo-controlled trial investigated the efficacy and safety of Gastrodia elata Blume (G. elata) in 100 participants aged 40–65 years with normal or impaired cognition. Participants received daily tablets, with primary outcome measured by the Alzheimer's Disease Assessment Scale-cognitive subscale (ADAS-cog). Secondary outcomes included K-MMSE, BDNF, amyloid β, and TAS. After 12 weeks, the G. elata group significantly improved ADAS-cog total scores (−2.15 ± 2.22) compared to the placebo group (−0.92 ± 2.03). Improvements were also noted in K-MMSE total score, BDNF, and TAS, but not amyloid β. No serious adverse events were observed. These results suggest that G. elata extract safely and effectively improved cognitive function in middle-aged adults with normal or mild cognitive impairment, making it a promising agent for cognitive decline prevention and management.